2004
DOI: 10.1007/978-3-540-40024-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Liquids in Confinement

Abstract: Abstract. Surface and confinement effects may have substantial effects on the molecular and collective dynamics of liquids. Within this chapter, we describe the confinement effects on the dynamical modes of isotropic liquids. Characteristic for many systems is the formation of surface layers with a retarded dynamics. Proper treatment of the adsorber walls ("lubrication") can reduce or completely remove such layers. In glass-forming liquids, the limiting space can lead to the suppression of the formation of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Additional loss peaks, attributed to molecules forming H-bonds to the inner pore surface, have also been reported from dielectric measurements of salol in 7.5 nm pores 48,49 . The work of Kremer and Stannarius 49 also revealed that the typical size of a shell of molecules interacting with the pore surface is about 2 or 3 molecules.…”
Section: A Dynamic Elastic Responsementioning
confidence: 55%
“…Additional loss peaks, attributed to molecules forming H-bonds to the inner pore surface, have also been reported from dielectric measurements of salol in 7.5 nm pores 48,49 . The work of Kremer and Stannarius 49 also revealed that the typical size of a shell of molecules interacting with the pore surface is about 2 or 3 molecules.…”
Section: A Dynamic Elastic Responsementioning
confidence: 55%
“…This observation is not surprising, considering the fact that the dimensions the glycerol molecules (∼0.47 nm in diameter, ∼0.52 nm in length, and with a hydrodynamic diameter of ∼0.6 nm) are only a factor of 4 smaller than the pore diameter (2.2 nm), and therefore, existence of separate dynamical populations across the pore diameter would probably be unphysical. This conjecture is corroborated by the fact that clear observation of bimodal dynamical heterogeneity was made in the dielectric relaxation of salol confined in pores with diameter (∼7.5 nm) about a factor 15 larger than the molecular diameter (∼0.5 nm) . Nevertheless, the possibility of the presence of significant dynamical heterogeneity in nanoconfined glycerol in the form of a wider spread of relaxation time scales compared to the bulk liquid cannot be completely ruled out.…”
Section: Resultsmentioning
confidence: 83%
“…This conjecture is corroborated by the fact that clear observation of bimodal dynamical heterogeneity was made in the dielectric relaxation of salol confined in pores with diameter (∼7.5 nm) about a factor 15 larger than the molecular diameter (∼0.5 nm). 34 Nevertheless, the possibility of the presence of significant dynamical heterogeneity in nanoconfined glycerol in the form of a wider spread of relaxation time scales compared to the bulk liquid cannot be completely ruled out. It may be noted in this regard that although a single value of τ NMR -1 , representative of the mean jump frequency, is used to simulate the 13 C static NMR line shape at each temperature, the upper limit of dynamical heterogeneity represented in these line shapes can be estimated by simulating these line shapes with a Gaussian distribution of τ NMR -1 values.…”
Section: Resultsmentioning
confidence: 99%
“…It is an often observed phenomenon, related to the increasing heterogeneity of relaxation dynamics under confinement, due to interactions between the sample and pore walls. 74,75 In the next step, dielectric loss spectra collected for APZ infiltrated into alumina and two kinds of silica templates (measured using two different thermal protocols described in the "Materials and Methods" section) were analyzed using the superposition of two Havriliak−Negami (HN) functions: 76 i k j j j j j y…”
Section: ■ Results and Discussionmentioning
confidence: 99%